Differential contribution of HP1 proteins to DNA end resection and homology-directed repair - Soria, Ramiro Gaston (2013)
Heterochromatin protein 1 paralogs (HP1α, β and γ in mammals) are not only central in heterochromatin organization, but have also been linked to transcriptional activation at euchromatic regions, maintenance of telomere stability and, most recently, to the DNA damage response (DDR). However, how HP1 proteins contribute to the DDR at a molecular level, and whether HP1 paralogs within the same organism, as well as their respective orthologs, have overlapping or unique roles in the DDR, remain to be elucidated. Herein, we have combined the analysis of the efficiency and kinetics of recruitment of key repair proteins to sites of DNA damage with specific DNA repair assays to demonstrate that human HP1 paralogs differentially modulate homology-directed repair (HDR) pathways, including homologous recombination (HR) and single-strand annealing (SSA). We find that while HP1α and β stimulate HR and SSA, HP1γ has an inhibitory role. In addition, we show that the stimulatory role of HP1α and β in HDR is linked to the DNA-end resection step of DNA breaks, through the promotion of RPA loading and phosphorylation at damage sites. Altogether, our findings provide mechanistic insight into how human HP1 proteins participate in the recombination process, emerging as important chromatin regulators during HDR.